My first ballet book - Castle, Kate. (Oxford : Kingfisher, 2011)
Introduces the world of ballet and presents its notable stories, dancers, techniques, and routines.
Includes index.
5.6
3-6.
3-6
Keywords: Ballet dancing -- Juvenile literature; Ballet -- Juvenile literature; Ballet dancing; Ballet; Ballet dancing; Ballet